THE SILENT WITNESS: THE JOURNEY OF CELIBACY IN THE LIFE OF DIOCESAN CLERGY OF PAGADIAN - Lague, Jumar T.; Tapanan, Enrique C; Leyte, Raven M.; Selgas, Jinggle C (Paradigma: Jurnal Kajian Budaya, 2025)
Celibacy is a defining vow in the life of Catholic priests, requiring thorough preparation and ongoing commitment. While celibacy enables priests to devote themselves fully to ministry, it also presents challenges that can influence their fidelity to priesthood. This study aimed to explore how Catholic priests experience, sustain, and interpret their vow of celibacy within their ministry. Using a transcendental phenomenological design, ten diocesan priests from Pagadian, representing junior, middle, and senior clergy, were purposively selected and interviewed. Data were collected through semi-structured interviews, validated with participant feedback, and analyzed thematically while bracketing researcher biases. The findings reveal that priests prepared for celibacy during seminary formation, but continued to face difficulties such as loneliness, temptation, and societal pressures. They relied on coping mechanisms, supportive relationships, and spiritual aspirations to remain faithful to their vow. Despite challenges, the participants affirmed their commitment to priestly ministry and identified celibacy as both a struggle and a source of deeper spiritual growth. The study concludes that sustaining celibacy requires not only personal resilience but also strong formation programs and community support. These insights are significant in addressing celibacy as a central factor in priestly vocation and retention.